Phytochemical, Nutraceutical Profiles and Potential of Soursop Leaf Extract (Annona muricata) on Bacterial Meningitis - Umaru, Isaac John; Danjuma, Tyem Lawal; Shadrach, Katchim Evelyn; Salman, Julius Ishaya; Mchibuma, Jibaniya Grace; Umaru, Kerenhappuch Isaac (African Journal of Medicine, Surgery and Public Health Research, 2026)
The rise of multidrug-resistant bacterial pathogens has intensified the search for alternative antimicrobial agents. Annona muricata (soursop), a tropical medicinal plant, has demonstrated promising antibacterial properties attributed to its rich phytochemical profile. However, the mechanistic basis of its antibacterial action remains underexplored. Aims: This study aimed to evaluate the mechanistic effects of A. muricata leaf extract on key bacterial targets, including cell wall integrity, membrane permeability, protein leakage, reactive oxygen species (ROS) generation, DNA fragmentation, and quorum sensing interference, using E. coli, S. aureus, and P. aeruginosa as representative strains. Materials and Methods: Fresh A. muricata leaves were extracted using ethanol and tested at a concentration of 100 mg/mL. Bacterial cultures were subjected to six mechanistic assays: crystal violet staining for cell wall integrity, propidium iodide and NPN fluorescence for membrane permeability, SDS-PAGE for protein synthesis inhibition, Bradford assay for protein leakage, DCFH-DA assay for ROS generation, and violacein quantification using the CV026 biosensor for quorum sensing interference. Ciprofloxacin served as a positive control, and untreated cultures served as a negative control. Results: The extract caused significant cell wall disruption (62.4%), comparable to ciprofloxacin (75.6%). Membrane permeability increased markedly, with PI and NPN fluorescence levels reaching 60–80% across strains. Protein leakage was elevated, with extracellular protein concentrations ranging from 25–30 µg/mL. SDS-PAGE revealed a 48.3–52.7% reduction in protein bands, indicating inhibition of protein synthesis. ROS levels surged to 8,000–9,500 RFU in treated samples, suggesting oxidative stress. DNA integrity scores dropped to 1–2, confirming genotoxic effects. Quorum sensing was inhibited by 68.9%, reducing violacein production and potential virulence. Conclusion: Annona muricata leaf extract exhibits potent antibacterial activity through multiple mechanisms, including structural disruption, metabolic interference, and oxidative damage. Its efficacy, comparable to ciprofloxacin in several assays, highlights its potential as a natural antimicrobial agent. These findings support further investigation into its bioactive compounds and therapeutic applications in combating resistant bacterial infections.